2020
DOI: 10.1007/s11748-020-01418-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve surgery for ischemic papillary muscle rupture: outcomes from the Japan cardiovascular surgery database

Abstract: Background Ischemic papillary muscle rupture (PMR) is a catastrophic complication following acute myocardial infarction (AMI). We evaluated early outcomes of PMR by using data from the Japan Cardiovascular Surgery Database, a nationwide Japanese registry. Methods We retrospectively analyzed data from 196 patients diagnosed with PMR following AMI in Japan between January 2014 and December 2017. Risk factors for operative mortality and severe complications following mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…This is likely to be due to a combination of edema, progression of tissue necrosis and lack of tensile strength in the ischemic tissues. Over the last three decades, apart from a reduction in the incidence of PMR to 0.07% from 1% to 5% as reported in the case series by Pahuja et al (37), there has not been a significant improvement in surgical in-hospital mortality which has largely remained in the region of 25% (11,13,14,18,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). This is unsurprising as the conduct of the surgery and mechanical circulatory support has largely remained unchanged.…”
Section: Mitral Valve Replacementmentioning
confidence: 99%
See 3 more Smart Citations
“…This is likely to be due to a combination of edema, progression of tissue necrosis and lack of tensile strength in the ischemic tissues. Over the last three decades, apart from a reduction in the incidence of PMR to 0.07% from 1% to 5% as reported in the case series by Pahuja et al (37), there has not been a significant improvement in surgical in-hospital mortality which has largely remained in the region of 25% (11,13,14,18,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). This is unsurprising as the conduct of the surgery and mechanical circulatory support has largely remained unchanged.…”
Section: Mitral Valve Replacementmentioning
confidence: 99%
“…Chordal sparing mitral valve replacement is more commonly carried out in the setting of acute PMR. Multiple case series have been published with reported in-hospital mortality of 20-25% (13,14). Similarly, 5-and 10-year survival of 65-68% and 32-56%, respectively (15)(16)(17).…”
Section: Mitral Valve Replacementmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the incidence of MCs has decreased due to the development of optimal medical therapies and reperfusion therapy, associated mortality rates have remained high. Several studies from Western countries [1][2][3][4][5] and Japan [6][7][8][9][10] have shown the MCs complicating MI in this era of percutaneous coronary intervention (PCI), but most of these studies only indicated the descriptive results of its incidence, treatment, and poor outcomes. In the superaged society in Japan, the proportion of older patients with MI is dramatically increasing.…”
mentioning
confidence: 99%